Tuning Redox Potential of Anthraquinone-2-Sulfonate (AQS) by Chemical Modification to Facilitate Electron Transfer From Electrodes in Shewanella oneidensis - Xu, Ning; Wang, Tai-Lin; Li, Wen-Jie; Wang, Yan; Chen, Jie-Jie; Liu, Jun (Frontiers in Bioengineering and Biotechnology, 2021)
Bioelectrochemical systems (BESs) are emerging as attractive routes for sustainable energy generation, environmental remediation, bio-based chemical production and beyond. Electron shuttles (ESs) can be reversibly oxidized and reduced among multiple redox reactions, thereby assisting extracellular electron transfer (EET) process in BESs. Here, we explored the effects of 14 ESs on EET in Shewanella oneidensis MR-1, and found that anthraquinone-2-sulfonate (AQS) led to the highest cathodic current density, total charge production and reduction product formation. Subsequently, we showed that the introduction of -OH or -NH2 group into AQS at position 1 obviously affected redox potentials. The AQS-1-NH2 exhibited a lower redox potential and a higher coulombic efficiency compared to AQS, revealing that the ESs with a more negative potential are conducive to minimize energy losses and improve the reduction of electron acceptor. Additionally, the cytochrome MtrA and MtrB were required for optimal AQS-mediated EET of S. oneidensis MR-1. This study will provide new clues for rational design of efficient ESs in microbial electrosynthesis.